Developing integrated natural sciences disaster mitigation model for elementary School Sintang - Wedyawati, Nelly (Universitas Negeri Makassar, 2017)
The purpose of the study are produce a proper textbook that can be used at school by knowing the process of learning on the implementation of Integrated Natural Sciences Disaster Mitigation textbook for students, to find the efectivity of textbook that is developed. The study is conducted by using research and development with Borg and Gall model. The stages five study development. Analysis of feasibility and book effectiveness are conducted by testing the normality, homogeneity, hypothesis, and textbook effectiveness. The results of the study show that (1) expert test on Integrated Natural Sciences Disaster Mitigation material is in Very Good qualification (94.4%) (2) expert test on teaching media is in Very Good qualification (96.3%) (3) book feasibility of the user is in Very Good qualification (85.9%) for teachers and Very Good qualification (90.1%) for students. (4) on limited and extensive trial show that the data is normal distributed but it is not homogeny that why then the researcher used Kruskall Wallis Test with p-level 0,000 is less than alpha 0,05 (p < 0,05). It means that there is influence of the implementation of Integrated Natural Sciences Disaster Mitigation textbook model on students’ achievement.